2021
DOI: 10.3844/ajbbsp.2021.40.49
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils from The Dropped Flowers of Camellia japonica: Extraction Optimization, Chemical Profile and Antibacterial Property

Abstract: Camellia japonica is one of the most economically valuable species that can be taxonomically placed in the Theaceae family. Many horticultural varieties of C. japonica have been cultivated as ornamental trees worldwide, owing to their charming flowers. However, young C. japonica flowers usually drop in a "decapitated" form during the peak flowering stage, causing a resource waste. In this study, Essential Oils from the Dropped C. japonica Flowers (EODCJF) were extracted with hydrodistillation and process was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…5-10). After discussing the key factors that affect the hydroxyl radicalscavenging rate of AROP and their interactions, the optimal process parameters were obtained and listed as follows: Pepsin amount of 2.0%, pepsin incubation time of 3.5 h, trypsin amount of 2.0% and trypsin incubation time of 3.0 h, under these conditions, the hydroxyl radicalscavenging rate of obtained APOR was 75.52±1.92%, when compared with predicted value, the relative deviation was ±1.42%, less than ±5.0%, suggesting that RSM along with BBD would be a feasible way to optimize the extraction conditions for APOR (Kong et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…5-10). After discussing the key factors that affect the hydroxyl radicalscavenging rate of AROP and their interactions, the optimal process parameters were obtained and listed as follows: Pepsin amount of 2.0%, pepsin incubation time of 3.5 h, trypsin amount of 2.0% and trypsin incubation time of 3.0 h, under these conditions, the hydroxyl radicalscavenging rate of obtained APOR was 75.52±1.92%, when compared with predicted value, the relative deviation was ±1.42%, less than ±5.0%, suggesting that RSM along with BBD would be a feasible way to optimize the extraction conditions for APOR (Kong et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…One-way analysis of variance (ANOVA) for fitting equation was described in Table 3. From Table 3, it can be observed that the P value of model was <0.0001 (P<0.01) and the P value of lack of fit was 0.3499 (P>0.05), indicating that (1) the fitting degree of this model is good; (2) unknown factors exert little influence on the results; (3) this model is stable and can well predict the actual changes of hydroxyl radical-scavenging rate of APOR (Kong et al, 2021). Coefficient of determination (R 2 ) was 0.9288, suggesting that 92.88% of the changes in response values derive from the selected variables.…”
Section: Model Establishment and Significance Testmentioning
confidence: 94%
“…As volatiles, CJS-EO is characterized by a pungent odor. It is synthesized by plants as secondary metabolites and has been widely used owing to its bactericidal, virucidal, fungicidal, anticancer, antioxidant, and antidiabetic activities [36]. e CJS-EO investigated in this study was primarily composed of hexamethylcyclotrisiloxane, which constituted 42.36% of the total chemical content.…”
Section: Discussionmentioning
confidence: 99%
“…2.4 (Shimadzu Corporation, Kyoto, Japan) was used to record and integrate the chromatograms. The EO components were identified by comparing their retention indices and mass spectra with those reported in different data base; NIST Mass Spectral Library (December 2011), Wiley Registry of Mass Spectral Data library (8th edition) and Adams (Adams 2009) as well as literature [52–55] …”
Section: Methodsmentioning
confidence: 99%